Towards a Decent Labour Market for Low-Waged Migrant Workers - Rijken, Conny; de Lange, Tesseltje (Amsterdam University Press, 2018)
Central to this edited volume is the legal position and the labour situation of non-EU and EU low-waged migrant workers. Towards a Decent Labour Market for Low-Waged Migrant Workers presents ground breaking research on policies and practices in search of striking a right balance between the economic ambitions and the negative consequences thereof, for labour market dynamics such as down-ward wage pressures, unfair competition, the abuse of migrant workers and even the long-term setback for the children of previously low-waged migrant workers. Imbalances or presumed imbalances between free market mechanisms, labour migration policies, labour market protection and corrective mechanisms to protect migrant workers, thus come to the fore. The contributors to this volume will deconstruct some of these imbalances, and shed light on its causes, consequences and interrelatedness with other factors. Possible solutions that contribute to a decent labour market, in which rights of low-waged migrant workers are more respected, will be discussed.